Transforming da'wah strategies during the Pandemic: Addressing religious community resistance to health protocols - Supena, Ilyas (Jurnal Ilmu Dakwah, 2024)
Purpose – This study aims to describe the forms and factors of resistance of religious communities to the application of health protocols during religious activities.Method – Data were collected by observing and interviewing Muslim community leaders who live in the village of Brumbung, Mranggen, Demak, Central Java, Indonesia. The concept of resistance approach is used to analyze the data descriptively and qualitatively.Results – This study shows that the form of resistance is carried out openly by implementing worship activities and activities of local religious traditions without complying with the COVID-19 pandemic protocol. In addition, the form of resistance is carried out in a closed manner through statements that describe a theocentric mindset, attitude, and belief. At the same time, the factors that influence resistance are traditional local religious leaders (kyai deso) and fatalistic religious understanding (jabbariyyah). Statements and social behavior of the kyai deso are counterproductive to efforts to prevent COVID-19.Implications – The consequences of this research have significant implications for public health and religious outreach in times of pandemics. The study points out a notable disparity between national religious guidelines and local religious customs, especially among Muslims in Java, Indonesia. Challenges in managing the pandemic arise from the reluctance to follow COVID-19 health measures influenced by traditional local religious leaders (kyai deso) and a fatalistic religious belief (jabbariyyah). This resistance is evident in both overt forms, such as ongoing communal religious practices, and covert means, like the maintenance of theocentric beliefs which contradict health guidelines.Originality/Value – Da’wah’s strategy for the prevention of COVID-19 must begin by contextualizing and re-actualizing religious messages that are more progressive and relevant to the findings of modern science about COVID-19, as well as involving local religious leaders in the process of socialization and internalization of religious understanding.***Tujuan – Penelitian ini bertujuan untuk mendeskripsikan bentuk dan faktor resistensi umat beragama terhadap penerapan protokol kesehatan dalam kegiatan keagamaan.Metode – Data dikumpulkan dengan cara observasi dan wawancara tokoh masyarakat Islam yang tinggal di Desa Brumbung, Mranggen, Demak, Jawa Tengah, Indonesia. Pendekatan konsep resistensi digunakan untuk menganalisis data secara deskriptif dan kualitatif.Hasil – Penelitian ini menunjukkan bentuk perlawanan dilakukan secara terbuka dengan melaksanakan kegiatan peribadatan dan kegiatan tradisi keagamaan setempat tanpa mematuhi protokol pandemi COVID-19. Selain itu, bentuk perlawanannya dilakukan secara tertutup melalui pernyataan-pernyataan yang menggambarkan pola pikir, sikap, dan keyakinan yang teosentris. Sedangkan faktor yang mempengaruhi resistensi adalah tokoh agama tradisional lokal (kyai deso) dan pemahaman agama yang fatalistik (jabbariyyah). Pernyataan dan perilaku sosial para kyai deso kontraproduktif terhadap upaya pencegahan COVID-19.Implikasi – Konsekuensi dari penelitian ini mempunyai implikasi yang signifikan terhadap kesehatan masyarakat dan jangkauan agama di masa pandemi. Studi ini menunjukkan kesenjangan yang mencolok antara pedoman agama nasional dan adat istiadat setempat, khususnya di kalangan umat Islam di Jawa, Indonesia. Tantangan dalam penanganan pandemi ini muncul dari keengganan untuk mengikuti langkah-langkah kesehatan COVID-19 yang dipengaruhi oleh tokoh agama tradisional setempat (kyai deso) dan keyakinan agama yang fatalistik (jabbariyyah). Perlawanan ini terlihat jelas dalam bentuk yang terang-terangan, seperti praktik keagamaan komunal yang masih berlangsung, dan cara-cara terselubung, seperti mempertahankan keyakinan teosentris yang bertentangan dengan pedoman kesehatan.Orisinalitas/Nilai – Strategi dakwah pencegahan COVID-19 harus dimulai dengan mengontekstualisasikan dan mengaktualisasikan kembali pesan-pesan keagamaan yang lebih progresif dan relevan dengan temuan ilmu pengetahuan modern tentang COVID-19, serta melibatkan tokoh agama setempat dalam proses sosialisasi dan internalisasi pemahaman agama.